The clinical significance of hyperglycemia in nondiabetic critically ill multiple trauma patients. (August 2018) - Koyfman, Leonid; Brotfain, Evgeni; Frank, Dmitry; Bichovsky, Yoav; Kovalenko, Inna; Benjamin, Yair; Borer, Abraham; Friger, Michael; Klein, Moti
Background: Information is inconsistent regarding the clinical role of acute elevations of blood glucose level secondary to hospital-acquired infections in nondiabetic critically ill patients during an intensive care unit stay. In this study we investigated the clinical significance of hyperglycemia related to new episodes of ventilator-associated pneumonia in nondiabetic critically ill multiple trauma intensive care unit patients. Materials and Methods: We analyzed the clinical data of 202 critically ill multiple trauma patients with no history of previous diabetes who developed a new ventilator-associated pneumonia episode during their intensive care unit stay. We used a time-from-event analysis method to assess whether acute changes in blood glucose levels that occurred prior to the onset of ventilator-associated pneumonia episodes had a different prognostic significance from those that occurred during such episodes. Glucose levels and other laboratory data were recorded for up to 5 days before ventilator-associated pneumonia events and for 5 days following these events. Results: Patients who required insulin therapy for persistent hyperglycemia related to a new ventilator-associated pneumonia event had a longer period of intensive care unit stay and a higher intensive care unit mortality rate than patients who did not require insulin for blood glucose control ( p < 0.008 and <0.001 respectively). In addition, older age, administration of parenteral nutrition, and elevated mean blood glucose level parameters on the day following the day of diagnosis of a new ventilator-associated pneumonia episode were found to be independent risk factors for intensive care unit mortality. Conclusion: Our study suggests that persistent hyperglycemia in nondiabetic critically ill patients, even treated by early insulin therapy, is an adverse prognostic factor of considerable clinical significance.